PENGARUH REAKSI HIDROGENASI PADA REFINED KERNEL STEARIN (RKS) - Merry Asria; Resi Wulandari (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2019)
Hydrogenation reaction in oil is the process of eliminating double bonds in oil by reacting H2 gas with oil, so that unsaturated oil turns into more stable saturated oil. The hydrogenation process in Refined Kernel Stearin (RKS) will produce Hydrogenated Kernel Stearin (HKS). Tested the composition of fatty acids, iodine numbers, melting points and solid fat content in RKS and HKS to see the effect of the hydrogenation reaction on RKS. The results showed a reduced double bond, resulting in a decrease in iodine number and an increase in melting point.